The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/s00148-020-00801-6
|View full text |Cite
|
Sign up to set email alerts
|

True COVID-19 mortality rates from administrative data

Abstract: In this paper, I use administrative data to estimate the number of deaths, the number of infections, and mortality rates from COVID-19 in Lombardia, the hot spot of the disease in Italy and Europe. The information will assist policy makers in reaching correct decisions and the public in adopting appropriate behaviors. As the available data suffer from sample selection bias, I use partial identification to derive the above quantities. Partial identification combines assumptions with the data to deliver a set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
0
24
1
3
Order By: Relevance
“… 8 Mortality rates from COVID-19 in Lombardia of Italy were known to be remarkably high. However, after controlling for selection bias, mortality rates ranged between 0.1 and 7.5%, which is far smaller than the 17.5% earlier reported (Depalo 2020 ). …”
contrasting
confidence: 65%
“… 8 Mortality rates from COVID-19 in Lombardia of Italy were known to be remarkably high. However, after controlling for selection bias, mortality rates ranged between 0.1 and 7.5%, which is far smaller than the 17.5% earlier reported (Depalo 2020 ). …”
contrasting
confidence: 65%
“…While according toDepalo (2020) and others, death rates might not have been in reality that high, the salient numbers of deaths discussed in the media and related public policy measures might have significantly affected the perceptions, mental health, and behavior of people, as pointed among others byQiu et al (2020);Milani (2020); and.…”
mentioning
confidence: 99%
“…They found that deaths recorded as directly due to COVID-19 constitute only half of the excess deaths verified in March. In comparison, Depalo ( 2021 ) applied partial identification to administrative data at the municipality level to estimate the number of deaths, the number of infections, and mortality rates from COVID-19 in Lombardy. He calculated that in March 2020, there were between 10,000 and 18,500 deaths, more than in the period 2015–2019.…”
Section: Literature Reviewmentioning
confidence: 99%